2007
DOI: 10.1590/s0004-282x2007000100010
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease in childhood: neuropsychological investigation of 14 cases

Abstract: -There are few studies about the development of a child after a cerebrovascular accident (CVA), and they usually describe problems such as diminishing in intellectual capacities, difficulties in linguistic and visual-motor skills, as well as in spatial organization and integration. In this study, there were 28 children participating, being 14 placed in the experimental group (EG) after clinical diagnosis and ischemic CVA imaging, and other 14 children without past history of CVA, who formed the control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
9
0
7
Order By: Relevance
“…Comparisons with theoretical population norms (M= 100, SD= 15) were used in studies when control groups were not included. The majority of studies found that children's scores on full scale IQ and index measures were significantly lower than the normative population means [58,31,14,33,34,47]. Performance IQ but not verbal IQ was significantly lower than the population mean in one study [21].…”
Section: Neuropsychological Outcomementioning
confidence: 80%
“…Comparisons with theoretical population norms (M= 100, SD= 15) were used in studies when control groups were not included. The majority of studies found that children's scores on full scale IQ and index measures were significantly lower than the normative population means [58,31,14,33,34,47]. Performance IQ but not verbal IQ was significantly lower than the population mean in one study [21].…”
Section: Neuropsychological Outcomementioning
confidence: 80%
“…This test is one of the most complex in clinical routine, since it is heavily linguistically loaded 14,19 , enabling more extensive neural network in each hemisphere. It reflects the effects of asymmetry in the processing of this type of stimulus ( for the benefit of the left hemisphere) and of the interhemispheric transfer rate 20 . Thus, because it is a task of great linguistic and cognitive demand, it would recruit neural networks of both hemispheres, responsible for sensory and high-order processing 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It reflects the effects of asymmetry in the processing of this type of stimulus ( for the benefit of the left hemisphere) and of the interhemispheric transfer rate 20 . Thus, because it is a task of great linguistic and cognitive demand, it would recruit neural networks of both hemispheres, responsible for sensory and high-order processing 20 . The greater demand would justify the performance difference between both dichotic tests, DD and SSW, in the competitive condition and, between competitive and non-competitive conditions of SSW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…90,91 Recurrence rates are high, justifying early diagnosis and primary or secondary preventative measures to reduce these complications. No standard treatment schemes have yet been proposed for managing stroke in children, with the majority of data having been drawn from consensus by specialists or extrapolated from reports in the literature on adult patients.…”
Section: Discussionmentioning
confidence: 99%